2003
DOI: 10.1038/sj.bjc.6600960
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance associated with loss of p53 involves extensive alterations in microtubule composition and dynamics

Abstract: In the present study, we compared the dynamics and composition of microtubules in cell lines derived from the human breast adenocarcinoma MCF-7 containing either the wild-type p53 (wt-p53; MN1) or a dominant-negative variant of p53 gene (mut-p53; MDD2). Mut-p53 cells were significantly resistant to the cytotoxicity of the microtubule-targeted drugs (vinca alkaloids and taxanes), as compared with wt-p53 cells. Studies by high-resolution time-lapse fluorescence microscopy in living cells indicated that the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 31 publications
1
42
0
1
Order By: Relevance
“…Cip1 and p27 Kip1 , which is frequently found in cancers, has been associated with alterations in microtubule dynamics (Baldassarre et al, 2005;Bouchet et al, 2011;Galmarini et al, 2003). The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…Cip1 and p27 Kip1 , which is frequently found in cancers, has been associated with alterations in microtubule dynamics (Baldassarre et al, 2005;Bouchet et al, 2011;Galmarini et al, 2003). The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…Taken together with EMSA results, p53 protein is thought to usually bind to this region to suppress mTUBB2 expression and that vincristine inhibits the binding of p53 to the response element, allowing for increased expression of class II h-tubulin. Other studies found that p53 transcriptionally downregulated microtubule-associated protein 4 (43) and that human breast adenocarcinoma cells harboring a mutated p53 gene displayed an increased level of class IV h-tubulin isotype and reduced levels of class I and II isotypes, suggesting that the p53 gene may differentially regulate expression of h-tubulin isotypes (28,29,32). These findings suggest that p53 could transcriptionally regulate components of the microtubule system.…”
Section: Discussionmentioning
confidence: 65%
“…It is well known that altered h-tubulin expression is associated with resistance to antimicrotubule drugs (7,8,18,29,37). Vinca alkaloid-resistant leukemia cells have been shown to display decreased class III h-tubulin isotype expression (8), whereas increased mRNA expression of class I, III, and IVa h-tubulin isotypes in Taxol-resistant sublines of epithelial ovarian tumors (22) and significant increases in class IVa h-tubulin isotype expression in Taxol-resistant canine osteosarcoma (37) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations